2013
DOI: 10.1590/s0102-79722013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Escolha do (a) parceiro (a) ideal por heterossexuais: são seus valores e traços de personalidade uma explicação?

Abstract: Resumo O presente estudo objetivou conhecer em que medida os valores humanos e os traços de personalidade se correlacionam com atributos desejáveis do(a) parceiro(a) ideal entre heterossexuais. Participaram 205 pessoas (100 mulheres e 105 homens) da população geral de João Pessoa (PB). Estes responderam aos seguintes instrumentos: Questionário dos Valores Básicos, Inventário dos Cinco Grandes Fatores e Escala de Atributos do Parceiro Ideal, além de perguntas sociodemográficas. Os valores se correlacionaram de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
6
0
8
Order By: Relevance
“…Sexual exposure is still the major transmission route for HIV, including prison inmates in Brazil, who are commonly ignored by preventive campaigns (19) . Studies have confirmed that receptive anal sexual intercourse has an increased risk of 1.4%, 18 times more in comparison with other practices (20)(21) . This practice is associated with homosexual relationships, but is also not rare in heterosexual relationships.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Sexual exposure is still the major transmission route for HIV, including prison inmates in Brazil, who are commonly ignored by preventive campaigns (19) . Studies have confirmed that receptive anal sexual intercourse has an increased risk of 1.4%, 18 times more in comparison with other practices (20)(21) . This practice is associated with homosexual relationships, but is also not rare in heterosexual relationships.…”
Section: Discussionmentioning
confidence: 87%
“…Among those who reported making selections, most did so based on trust and attractive physical appearance, which was statistically associated with HIV infection. In this form of selection, participants trusted that people they knew did not have STI, as though attractive physical appearance meant protection or exemption from disease, or that the physical appearance of partners in that moment was more important than protection of their own health (21) . Most seropositive individuals did not use condoms or only used them sometimes, suggesting that their current serological status may have had a direct link with these practices.…”
Section: Discussionmentioning
confidence: 99%
“…In studies about the choice of ideal partners for a relationship (48)(49) , it is seen that women value traits related to the financial stability potential that men will have in the future, i.e., traits that show more resources to be invested in them and their future children. They also value men's ability to protect them physically and their potential to become good fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Em se tratando de atração interpessoal, a beleza física assume status de elemento central, embora nem sempre expressado socialmente, devido a seu caráter potencialmente contranormativo (Adams, 1977;Byrne, 1971;Camargo et al, 2005;Camargo et al, 2007;Feingold, 1990;Gomes & Caramaschi, 2007;Gomes, Gouveia, Silva Júnior, Coutinho & Santos, 2013;Gottschall, 2008;Krebs & Adinolfi, 1975;Langmeyer & Shank;1995;Lemay, Clark & Greenberg, 2010;Murstein, 1972;Stojanowska, 2003;Tanke, 1982;Schlösser & Camargo, 2015).…”
Section: Considerações Finaisunclassified